Spin Cross-Over (SCO) Anionic Fe(II) Complexes Based on the Tripodal Ligand Tris(2-pyridyl)ethoxymethane - Emmelyne Cuza; Samia Benmansour; Nathalie Cosquer; Françoise Conan; Sébastien Pillet; Carlos J. Gómez-García; Smail Triki (Magnetochemistry, 2020)
Reactions of Fe(II) with the tripodal chelating ligand 1,1,1-tris(2-pyridyl)ethoxymethane (py3C-OEt) and (NCE)− co-ligands (E = S, Se, BH3) give a series of mononuclear complexes formulated as [Fe(py3C-OEt)2][Fe(py3C-OEt)(NCE)3]2·2CH3CN, with E = S (1) and BH3 (2). These compounds are the first Fe(II) spin cross-over (SCO) complexes based on the tripodal ligand tris(2-pyridyl)ethoxymethane and on the versatile co-ligands (NCS)− and (NCBH3)−. The crystal structure reveals discrete monomeric isomorph structures formed by a cationic [Fe(py3C-OEt)2]2+ complex and by two equivalent anionic [Fe(py3C-OEt)(NCE)3]− complexes. In the cations the Fe(II) is facially coordinated by two py3C-OEt tripodal ligands whereas in the anion the three nitrogen atoms of the tripodal ligand are facially coordinated and the N-donor atoms of the three (NCE)− co-ligands occupy the remaining three positions to complete the distorted octahedral environment of the Fe(II) centre. The magnetic studies show the presence of gradual SCO for both complexes: A one-step transition around 205 K for 1 and a two-step transition for compound 2, centered around 245 K and 380 K.